Centering Black life in Canadian early childhood education. Issue 2 (17th February 2023) - Nxumalo, Fikile; Pacini-Ketchabaw, Veronica
ABSTRACT: This paper is a response to multiculturalism's reductionist and othering constructions of Black presence in Canadian early childhood research and practice. We engage in possibilities for creating movement away from multiculturalism as the primary way of responding to anti-Blackness in Canadian early childhood education. We put forward orientations that emerge when we imagine the abolition of Canadian early childhood education pedagogies and curriculum that are shaped by neoliberal multiculturalism. We organize our abolitionist praxis in relation to what kinds of stories and modes of storytelling of Black life might be needed in early childhood education in Canada. We focus our attention on three interconnected pedagogical orientations: storying abolition geographies, storying Black ecologies, and storying Black aliveness.